(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article provides theoretical and practical insights into the role of logistics in public procurement, interlinguistic, linguistic analysis and improvement of theoretical aspects of the process of public and corporate procurement and their transportation and delivery services.